Political Resolution of New India Coalition - New India Coalition:::Creator::::::::::::
This pamphlet addresses the poor living and working conditions of Indian workers and peasants in the 1970s, the strong influence of imperialism, and the suspension of civil liberties. It calls for structural change to the hierarchical class structure.